Fabrication of IrxTa100−xOy as counter electrodes in saline water. (18th October 2022) - Lee, Na Yeon; Im, Han Seo; Lee, Sumin; Lee, Hyun Joo; Choi, Hyun Seung; Lim, Sung Yul
Abstract: One of the key challenges to realize electrolysis of seawater is to develop highly active and stable electrocatalysts in oxygen evolution reaction (OER). This is crucial even for the development of electrocatalysts for hydrogen evolution reaction (HER) using three‐electrode configuration because damaged surfaces of counter electrodes (CEs), which exposed to electrochemical oxidative environments often limit the performance of cathodes in working electrodes (WEs) by lowering the electrical conductivity and poisoning the surface of electrocatalysts. Herein, we demonstrate the use of Ir x Ta100− x O y as a CE in simulated seawater. Ir x Ta100− x O y ‐coated electrodes as CEs with optimized Ir:Ta ratios enable the high‐valence states of Ir for improving activity and selectivity toward the OER. Moreover, the Ir x Ta100− x O y CEs ensure unhindered electrochemical performance of Pt for HER in contrast to carbon‐based materials, thus highlighting their reliability as a CE. Abstract : Ir x Ta100− x O y ‐coated electrodes were fabricated by dip coating and thermal treatment. This electrode was used as a counter electrode (CE) to evaluate activities of electrocatalysts toward hydrogen evolution reaction (HER) in simulated seawater. Constant activities for Pt‐based electrodes in HER were observed implying the reliability of the Ir x Ta100− x O y as CE to prevent from deceptive measurements of HER performance.